2012
DOI: 10.1508/cytologia.77.107
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Analysis of Mehr Cotton Cultivar and Its Crossing Progenies: A Search for Unreduced Pollen Grains

Abstract: SummaryCotton is cultivated in Iran with diploid and tetraploid forms and hybridization is a means to increase the genetic diversity and obtain new elite cultivars in this crop. The present study considers cytogenetic study of the Mehr (Gossypium hirsutum) cotton cultivar and its crossing progenies. The cultivars showed bivalents, univalents and quadrivalents in metaphase of meiosis I. They differed significantly in mean values of chiasmata formation and chromosome pairing due to genetic difference. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Furthermore, Skovsted (1934), working on the production of hybrids between diploid Asiatic and tetraploid New World cotton, obtained a hybrid with 52 chromosomes, and hypothesized the production of 2 n gametes in the diploid parent. Likewise, in cytogenetic studies of cotton cultivars grown in Iran, the occurrence of large pollen grains was assumed to be potential unreduced gametes (Sheidai 2008; Noormohammadi et al 2012), although other methods are considered to be necessary to confirm the correlation between size and ploidy in pollen (Dewitte et al 2012). For the same type of sterile hybrids (triploids 2 n  = 39, one tetraploid 2 n  = 52) obtained by crossing A-genome Asiatic cottons with tetraploid New World cottons, Amin (1940) reported that backcrossing to New World cottons gave occasional success in boll setting on the F1s.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Skovsted (1934), working on the production of hybrids between diploid Asiatic and tetraploid New World cotton, obtained a hybrid with 52 chromosomes, and hypothesized the production of 2 n gametes in the diploid parent. Likewise, in cytogenetic studies of cotton cultivars grown in Iran, the occurrence of large pollen grains was assumed to be potential unreduced gametes (Sheidai 2008; Noormohammadi et al 2012), although other methods are considered to be necessary to confirm the correlation between size and ploidy in pollen (Dewitte et al 2012). For the same type of sterile hybrids (triploids 2 n  = 39, one tetraploid 2 n  = 52) obtained by crossing A-genome Asiatic cottons with tetraploid New World cottons, Amin (1940) reported that backcrossing to New World cottons gave occasional success in boll setting on the F1s.…”
Section: Discussionmentioning
confidence: 99%